2010
DOI: 10.1111/j.1365-2109.2010.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of non-specific immune responses and disease resistance on oral administration of Nyctanthes arbortristis seed extract in Oreochromis mossambicus (Peters)

Abstract: The immunomodulatory effect of the seed extract of an Indian medicinal plant Nyctanthes arbortristis L. (NAT) on non‐specific immune responses and disease resistance of tilapia, Oreochromis mossambicus was investigated. Chloroform extract was administered orally as a feed supplement at doses of 0.01%, 0.1% or 1% for 3 weeks. Non‐specific immune parameters such as serum lysozyme and alternate complement haemolytic (ACH50) activities, and cellular reactive oxygen species (ROS), reactive nitrogen intermediate (RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…In our study, lysozyme activity was significantly increased only in the diet supplemented with fenugreek. Kirubakaran et al (2010) reported that herb addition increased the level of myeloperoxidase in O. mossambicus; likewise we have proved in our study. Previous studies showed that tilapias fed a diet including Cinnamomum verum, Andrographis paniculata (Rattanachaikunsopon and Phumkhachorn 2009), Rosmarinus officinalis (Zilberg et al 2010) and Cuminum cyminum (Yılmaz et al 2012) increased the survival rate against streptococcal challenge.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, lysozyme activity was significantly increased only in the diet supplemented with fenugreek. Kirubakaran et al (2010) reported that herb addition increased the level of myeloperoxidase in O. mossambicus; likewise we have proved in our study. Previous studies showed that tilapias fed a diet including Cinnamomum verum, Andrographis paniculata (Rattanachaikunsopon and Phumkhachorn 2009), Rosmarinus officinalis (Zilberg et al 2010) and Cuminum cyminum (Yılmaz et al 2012) increased the survival rate against streptococcal challenge.…”
Section: Discussionsupporting
confidence: 78%
“…Levels of lysozyme can be increased after supplementation of O. niloticus and O. mossambicus with herbs such as Astragalus membranaceus, Lonicera japonica (Ardó et al 2008) and Nyctanthes arbortristis (Kirubakaran et al 2010). In our study, lysozyme activity was significantly increased only in the diet supplemented with fenugreek.…”
Section: Discussionmentioning
confidence: 99%
“…Common parts can be used viz. fruit (Massa medicate) (Takaoka et al, 2011), fruit (Piper guineese) and seed (Xylopia aethiopica) (Okeke et al, 2001), leaves Micol et al, 2005;Sudhakaran et al, 2006), roots (Wang et al, 2011), seeds (Kirubakaran et al, 2010;Sivaram et al, 2004), flowers (PerazaGómez et al, 2011), or powders, which can be purchased from markets (Kim et al, 1999;Radhakrishnan et al, 2014;Sahu et al, 2008). Some herbs used in aquaculture are in the form of extract compounds such as Astragalus radix (from Astragalus membranaceus) and Scutellaria radix (from Scutellaria baicalensis) (Yin et al, 2006), and anthraquinone extract (from Rheum officinale Bail) (Liu et al, 2010) are commonly used in aquaculture because of their ability to enhance fish immune systems.…”
Section: Sources Of Medicinal Plantsmentioning
confidence: 97%
“…To reduce or avoid the dependence of aquaculture on antibiotics, some products of natural plant origin have been considered as an effective alternative way to control bacterial and viral infections (Harikrishnan et al 2010;Kirubakaran et al 2010). Several antimicrobial, anti-stress, immunostimulant and growth-promoting plant products significantly influence the health of fish (Dada and Ikuerowo 2009).…”
mentioning
confidence: 99%